2006
DOI: 10.1007/s11103-006-9064-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the plant Notchless homolog, a WD repeat protein involved in seed development

Abstract: We have isolated a plant NOTCHLESS (NLE) homolog from the wild potato species Solanum chacoense Bitt., encoding a WD-repeat containing protein initially characterized as a negative regulator of the Notch receptor in animals. Although no Notch signaling pathway exists in plants, the NLE gene is conserved in animals, plants, and yeast. Overexpression of the plant ScNLE gene in Drosophila similarly affected bristle formation when compared to the overexpression of the endogenous Drosophila NLE gene, suggesting fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 69 publications
3
24
0
Order By: Relevance
“…This discrepancy could be explained by RNA interference showing different levels of effectiveness on the NLE gene in the sporophytic tissues of these two plant species. While clear reduction in ScNLE transcript levels was detected in S. chacoense transformants (Chantha et al, 2006), this was not the case for AtNLE transcripts in Arabidopsis transformants. Another explanation could be that Arabidopsis sporophytic development is more sensitive to changes in AtNLE expression levels and could not survive to an important reduction in transcript levels.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…This discrepancy could be explained by RNA interference showing different levels of effectiveness on the NLE gene in the sporophytic tissues of these two plant species. While clear reduction in ScNLE transcript levels was detected in S. chacoense transformants (Chantha et al, 2006), this was not the case for AtNLE transcripts in Arabidopsis transformants. Another explanation could be that Arabidopsis sporophytic development is more sensitive to changes in AtNLE expression levels and could not survive to an important reduction in transcript levels.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, the semisterility phenotype was maintained in the following generations. Previous studies reported that RNA interference is not always associated to detectable reduction in targeted gene transcript levels (Kerschen et al, 2004) and that levels of residual targeted gene transcript are not necessarily correlated to degree of phenotype severity (Acosta-Garcia and Chantha et al, 2006). In cleared ovules of the AtNLE-RNAi lines analyzed, female gametophytes in proportions corresponding to levels of aborted ovules were either degenerated or arrested at early developmental stages, including as early as during the megaspore forming stage (FG0) and with a predominance at the one-nucleate (FG1) stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, two homologs of the Drosophila melanogaster NOTCHLESS gene involved in cell fate decision and developmental processes through the Notch pathway and ribosomal biogenesis were also upregulated from 24 h (NLE and NLE1). NOTCHLESS plant homologs have been shown to regulate cell growth and proliferation (Chantha et al, 2006). Another gene that regulates ribosomal biogenesis (RRS1) also clustered in C3.…”
Section: Protein Biosynthesis Reorientation During Protoplast Culturementioning
confidence: 99%